2004
DOI: 10.1097/01.ju.0000138529.43179.dd
|View full text |Cite
|
Sign up to set email alerts
|

Results of Tapered Ureteral Reimplantation for Primary Megaureter: Extravesical Versus Intravesical Approach

Abstract: Extensive ureteral tailoring with an extravesical ureteral reimplantation may be performed safely and effectively for primary obstructive megaureter. Patients with voiding dysfunction or preoperative vesicoureteral reflux may benefit from an intravesical ureteral reimplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…However, recent studies showed that ET for grade V offered higher success rate than open reimplantation with only 3.6% failure rate and 5.4% recurrence rate (35). Such a success rate was higher than found after open ureteral reimplantation for grade V which was shown to be 80.7% with higher complication rate (36,37). In a study conducted by Tsai et al cases who developed failure to ET had associated risk factors (21).…”
Section: Discussionmentioning
confidence: 80%
“…However, recent studies showed that ET for grade V offered higher success rate than open reimplantation with only 3.6% failure rate and 5.4% recurrence rate (35). Such a success rate was higher than found after open ureteral reimplantation for grade V which was shown to be 80.7% with higher complication rate (36,37). In a study conducted by Tsai et al cases who developed failure to ET had associated risk factors (21).…”
Section: Discussionmentioning
confidence: 80%
“…13 Tailoring and reimplantation could be unfeasible because of the small bladder capacity in these patients. 7 As Defoor and colleagues 7 have noted, tailoring and implantation before the age of 1 year can potentially compromise the vascularity of the distal ureter and can result in further stricture.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the above-mentioned advantages of these modifications, the folded ureter is bulky and may make the reimplantation difficult. 7 Open surgery is usually associated with significant postoperative pain, long hospital stay, prolonged convalescence, and remaining unsightly scars.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our success rate equals or exceeds the cure rates achieved by open surgery. 5,[19][20][21][22][23][24] Besides, the costs are reduced prominently compared with open surgery.…”
Section: Discussionmentioning
confidence: 98%
“…5,18 The complications of the classic methods are well known, with rates ranging from 4% to 25% in different series. 5,[19][20][21][22][23][24] An important complication of both techniques is stricture secondary to damage to the thin and fragile ureteral vessels. 25 Strictures also may follow plication techniques, probably because of compression of the vessels by the folded wall.…”
Section: Discussionmentioning
confidence: 99%